Personalizing the design of computer-based instruction to enhance learning - Hitendra Pillay; Wageeh Boles; Leonard Raj (Association for Learning Technology, 1998)
The continued innovations in multimedia technology and powerful programming software ensure that computer-based instruction (CBI) will become an integral part of our teaching and learning process and a dominant educational delivery system in many parts of the world (Boric, 1991). Yet despite the popularity of CBI material, there is a gap in understanding of the relationship between multimedia and learning. Kozma (1994) argues that any understanding of the relationship between media and learning must be grounded in cognitive and social processes associated with knowledge construction. Due to a lack of understanding of the relationship between learning and multimedia, the incentive for developing CBI packages has been the innovative alternative in information technology for presenting instructional material rather than learning theories (Ambron and Hooper, 1990). Hence, Hedberg, Harper and Brown (1993) have called for a closer examination of ways in which information is accessed and processed in current learning packages as a basis for designing CBI packages for effective learning outcomes.